Nutrilac: Aplicativo para Elaboração de Dietas de Bovinos de Leite - Nascimento, Deivid Duarte; Ferreira, Marcos Paulo Priamo; Maia, Brian Luís Coimbra; Vita, Maria Carolina da Silva; Faria, Alexandra Calda Cézar de; Franca, Almira Biazon; Chaves, Amália Saturnino; Maciel, Luiz Maurílio da Silva; Goliatt, Priscila Vanessa Zabala Capriles (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Animal nutrition is responsible for a large part of the expenses in a farm and, most of the time, it is neglected by producers, which leads to increased spending on unbalanced diets. Thus, the present work seeks to bring to small and medium-sized rural producers a mobile application capable of formulating the ration of dairy cattle in an easy and simple way, ensuring compliance with nutritional requirements and seeking a diet of minimal cost, from foods chosen by the user.